ANALISA PERBANDINGAN DUA MEREK SEMEN DENGAN KEBERSIHAN MATERIAL TERHADAP KUAT TEKAN BETON K-250 - DONI RINALDI BASRI (LPPM Universitas Abdurrab, 2019)
Concrete is a material that is often used in building construction, because concrete is easily made in accordance with the desired shape and the material used is widely available in nature. The materials used in making concrete are sand, gravel / split, water and cement as a binder. Concrete materials are obtained in nature mixed with other substances such as plants, plastics, mud and others. The quality of concrete is influenced by the materials used and the cleanliness of the material. This study examines the effect of material cleanliness on the quality of the concrete produced. The sand material comes from Bingkuang lake in Kampar district, this stone from stone in Kampar district, water from bore wells and adhesives is used from two suppliers. The planned concrete is K-250. Cleanliness of the material by washing and not being washed. The age of the concrete was analyzed at 7 days, 14 days and 28 days. The results of analysis using brand A binder with the cleaned material obtained concrete quality K-281.75 and using unclean materials obtained concrete quality K-217.15. There was a reduction in concrete quality of 22.93%. The analysis results using brand B binder with cleaning agent, K-303,84 concrete quality and using uncleaned material, K-203,40 concrete quality. There was a decrease in the quality of concrete by 33.06%. Thus the use of non-clean materials can reduce the quality of concrete by 20-30%.